2011
DOI: 10.1037/a0023866
|View full text |Cite
|
Sign up to set email alerts
|

Imitation in young children: When who gets copied is more important than what gets copied.

Abstract: Unlike other animals, human children will copy all of an adult's goal-directed actions, including ones that are clearly unnecessary for achieving the demonstrated goal. Here we highlight how social affiliation is key to this species-specific behavior. Preschoolers watched 2 adults retrieve a toy from a novel apparatus. One adult included irrelevant actions in her demonstration; the other only used actions causally related to opening the apparatus. After both adults took turns demonstrating, 1 left the test roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
221
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 244 publications
(239 citation statements)
references
References 25 publications
(24 reference statements)
13
221
1
4
Order By: Relevance
“…Consequently, it is necessary to be interpret these findings in a context of the goaldirected imitation literature with some caution. In detecting a contraction bias, we find that children are imitating conservatively, which appears at some odds with literature suggesting that children are more likely to over-imitate (Horner & Whiten, 2005;McGuigan et al, 2010) and that they may do so to comply with prescriptive norms or cultural expectations (Kenward, Karlsson, & Persson, 2011;Nielsen & Blank, 2011). In our study however, the degree of error was not the result of intentional action selection but rather a mismatch between magnitudes of perceived and executed actions, presumably as a result of the functioning of the visuomotor system.…”
Section: Discussioncontrasting
confidence: 56%
“…Consequently, it is necessary to be interpret these findings in a context of the goaldirected imitation literature with some caution. In detecting a contraction bias, we find that children are imitating conservatively, which appears at some odds with literature suggesting that children are more likely to over-imitate (Horner & Whiten, 2005;McGuigan et al, 2010) and that they may do so to comply with prescriptive norms or cultural expectations (Kenward, Karlsson, & Persson, 2011;Nielsen & Blank, 2011). In our study however, the degree of error was not the result of intentional action selection but rather a mismatch between magnitudes of perceived and executed actions, presumably as a result of the functioning of the visuomotor system.…”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, since faithful imitation is often related to the social context at the time of the demonstration and response (e.g., Nielsen & Blank, 2011;Nielsen, Simcock, & Jenkins, 2008;Over & Carpenter, 2009; see also work on conformity and audience effects, e.g., Haun & Tomasello, 2011), manipulating, for example, who is watching when could also be informative. It might also be interesting to manipulate the type of tool used in the demonstration.…”
Section: Discussionmentioning
confidence: 99%
“…Social cues, such as demonstrator status, have been shown to modulate overimitation. For example, it has been shown that children will only reproduce irrational actions when being observed by the demonstrator (Lyons et al, 2007;Nielsen & Blank, 2011). This suggests that overimitation is an important social behavior, and motivates us to explore its neural mechanisms.…”
Section: Overimitation Behaviormentioning
confidence: 99%
“…Implicit mimicry is always likely to be more subtle than explicit copying. Second, overimitation is very much a social behavior, which occurs most commonly in social context such as being watched by an experimenter (Nielsen & Blank, 2011). To maintain tight experimental control, the social context of the current study was minimal.…”
Section: Behavioral Datamentioning
confidence: 99%